Contact heterogeneities in feral swine: implications for disease management and future research. Issue 3 (17th March 2016) - Pepin, Kim M.; Davis, Amy J.; Beasley, James; Boughton, Raoul; Campbell, Tyler; Cooper, Susan M.; Gaston, Wes; Hartley, Steve; Kilgo, John C.; Wisely, Samantha M.; Wyckoff, Christy; VerCauteren, Kurt C.
Abstract: Contact rates vary widely among individuals in socially structured wildlife populations. Understanding the interplay of factors responsible for this variation is essential for planning effective disease management. Feral swine ( Sus scrofa ) are a socially structured species which pose an increasing threat to livestock and human health, and little is known about contact structure. We analyzed 11 GPS data sets from across the United States to understand the interplay of ecological and demographic factors on variation in co‐location rates, a proxy for contact rates. Between‐sounder contact rates strongly depended on the distance among home ranges (less contact among sounders separated by >2 km; negligible between sounders separated by >6 km), but other factors causing high clustering between groups of sounders also seemed apparent. Our results provide spatial parameters for targeted management actions, identify data gaps that could lead to improved management and provide insight on experimental design for quantitating contact rates and structure.